Pengaruh Customer Dissatisfaction dan Word of Mouth (WOM) Terhadap Brand Switching pada California Fried Chicken (CFC) ke Fast Food Merek Lain (Studi Kasus pada Masyarakat Kota Padang) - Mufira Widianti; Okki Trinanda (Jurnal Kajian Manajemen dan Wirausaha, 2019)
This research is motivated by the emergence of the phenomenon of society that tends to shift brands especially in the fast food category. This research aims to analyze the effect of customer dissatisfaction and word of mouth (WOM) on brand switching in humanity of Padang city. The population in study are humanity of Padang city who had consumed fast food CFC then switched to another brand. While the sample is determined by purposive sampling method, in order to obtain a sample of 100 respondents. Data used in this research are primary ones which obtained from questionnaire. Data analysis method used multiple regression analysis and tested using the SPSS version 15.0 application. This study founds that the independent variables that have significant effect and the probability of dependent variables. The result showed accurately prediction as much as 45,2%. Keywords: Brand Switching, Customer Dissatisfaction, Word of Mouth (WOM)